Efektivitas NDT dalam Mengontrol Tingkat Spastisitas dan Meningkatkan Kemampuan Gross Motor Anak dengan Kondisi CP - Desy Wahyu Utami; Isnaini Herawati (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Introduction: Cerebral palsy is a condition in which the brain is damaged, resulting in a crucial abnormality because the brain is the center of human activity. The severity of cerebral palsy is classified into 4 categories, namely mild, moderate, severe, and no cerebral palsy. will affect the level of spasticity and gross motor skills of children. Children with cerebral palsy experience gross motor disorders which result in limitations in carrying out activities so that interventions are needed to support the gross motor development of children with cerebral palsy. NDT is a common intervention given to children with physical development disorders. This intervention focuses on normalizing hypertone muscles. Objective: To determine the effectiveness of NDT in controlling spasticity and improving gross motor skills in children with cerebral palsy. Methods: The study used a single-subject research conducted on children with cerebral palsy. This research was conducted for 3 weeks and the treatment was carried out 6 times with the provision of neuro development treatment interventions.Results: The evaluation was carried out using the Ashworth scale and GMFM measurement instruments. After 6 treatment sessions, there was a decrease in the level of spasticity and an increase in gross motor ability. Conclusion: The results showed that the Neuro Development Treatment was effective in controlling the level of spasticity and increasing the gross motor ability of children with cerebral palsy. Keywords: Cerebral palsy, neuro development treatment, spastisitas, gross motor